The interactive effects of pre-pregnancy body mass index, thyroid function, and blood lipid levels on the risk of gestational diabetes mellitus: a crossover analysis - Ying Wang; Sha Lu; Xianrong Xu; Lijun Zhang; Jun Yang; Wensheng Hu (BMC, 2022)
Abstract Background Studies have demonstrated the associations between pre-pregnancy obesity, thyroid dysfunction, dyslipidemia, and increased risk of gestational diabetes mellitus (GDM) in pregnant women. This study was designed to investigate whether and to what extent, the interactions between these factors contribute to the risk of GDM. Methods A case-control study of 232 GDM cases and 696 controls was conducted among pregnant women from Hangzhou, China. Multiple logistic regression analysis was applied to identify independent risk factors of GDM. Crossover analysis was performed to assess the interactive effects of pre-pregnancy body mass index (pBMI), thyroid hormones, and blood lipid profiles on the risk of GDM. The indexes including attributable proportion (AP) to the interaction and the relative excess risk due to interaction (RERI) were calculated. Results Chinese pregnant women with pBMI > 23 kg/m2 (adjusted: OR = 4.162, p < 0.001), high triglyceride levels (> 2.30 mmol/L) (adjusted: OR = 1.735, p < 0.001), and the free triiodothyronine/free thyroxine (FT3/FT4) ratio ≥ 0.502 (OR = 4.162, p < 0.001) have significantly increased risk of GDM. Crossover analysis indicated that there were significant interactions between pre-pregnancy overweight/obesity and FT3/FT4 ≥ 0.502 (AP = 0.550, p < 0.001; RERI = 7.586, p = 0.009), high TG levels and FT3/FT4 ≥ 0.502 (AP = 0.348, 95%CI = 0.081-0.614, P = 0.010; RERI = 2.021, 95%CI = 0.064-3.978, p = 0.043) on the risk of GDM. Conclusion The interactions between pBMI and FT3/FT4 ratio, TG level and FT3/FT4 ratio may have significant impacts on the risk of GDM in pregnant women. Such findings may help improve our understanding of the pathogenesis of GDM as well as develop comprehensive strategies for the management of GDM.